The Application of Tengganai Permission in Traditional Marriage Processes: A Review of Al-‘Adah al-Muhakkamah - Yumna Sakinah Lubis; Widiya Yul; Masrur Masrur (International Journal of Multidisciplinary Research of Higher Education, 2026)
Indonesia possesses a diverse array of customary laws that remain vibrant and evolving within its communities. However, not all customary legal practices can automatically serve as a legal basis from an Islamic legal perspective. This study aims to fill a gap in the literature by explaining how the principle of al-‘Adah al-Muhakkamah views the application of customary law as practiced in society, particularly in the context of customary marriage. This study employs a qualitative method using a case study approach, with data collection techniques including interviews, observations, and document analysis. The research location is in a specific region within Jambi Province, Indonesia. The findings reveal that the customary law in effect among a particular community group in the Jambi region requires a letter of permission (tengganai permit) as one of the administrative prerequisites for processing a marriage referral letter at the village level. From the perspective of al-‘Adah al-Muhakkamah, this customary practice does not conflict with Islamic law; it applies generally to the community, is consistently enforced, and has been passed down through generations. In addition to serving as an administrative formality, the requirement for a tengganai permit also functions as a protective mechanism for women and nieces, as well as a form of customary social control to ensure the man’s responsibility before the marriage takes place. The implications of this research indicate that the implementation of the tengganai permit can serve as a model for integrating customary law and Islamic law that safeguards the welfare and dignity of marriage. Furthermore, this practice underscores the importance of local wisdom as a social protection mechanism that aligns with religious principles and state regulations.